(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study on the soil chemical properties response to regular application of agrochemicals was carried out in rice farms at Ifite-Ogwari. Soil samples were taken from rice field that receives various forms of agrochemical and that of adjacent field as control using random sampling techniques at depths of 0-15cm and 15-30cm in three replicates. Sampled soils were air dried, sieved and analyzed in the laboratory using standard routine procedures. Heavy metals As and Pb were analyzed in the laboratory using double acid method. The rest showed that pH was strongly acidic both at soils with applied agrochemicals (rice field) and control, 5.41 and 5.12 respectively. The control also recorded high organic carbon (1.90%), while soil with applied agrochemicals (rice field) had the lowest organic carbon (1.01%); so also, was total nitrogen. Calcium content was low ranging from 2.27 to 4.80Cmolkg-1; magnesium content was moderate ranging from 1.20 to 2.27Cmolkg-1; potassium was very low ranging from 0.14 to 0.19Cmolkg-1; sodium was also very low ranging 0.09 to 0.15Cmolkg-1. Available phosphorus showed low to medium, 3.63mg/kg and 10.4mg/kg respectively. Heavy metals studied also showed that arsenic (As) content which was between 0.01 to 0.16mgkg-1 and lead (Pb) 0.13 to 0.22mgkg-1 didn’t reach the permissible limit given by FAO. The study showed that calcium, available phosphorus, soil pH and arsenic concentration responded significantly to the regular use of agrochemicals in the rice farm.